Phoresy of astigmatic mites on ticks and fleas in Poland - Karbowiak, Grzegorz; Solarz, Krzysztof; Asman, Marek; Wróblewski, Zbigniew; Slivinska, Kateryna; Werszko, Joanna (Biological Letters, 2014)
Phoresy is an association in which a small animal clings to a larger one exclusively for transportation. We searched for phoretic mites on fleas and ticks of small mammals. A total of 169 fleas of 7 species were collected in the Białowieża Forest (E Poland) and in Kosewo G órne (NE Poland) in July and August in 2007 and 2008. Moreover, 20 nymphs and 12 females of Ixodes hexagonus (Leach, 1815) were collected in the beaver farm of the Research Station of Polish Academy of Sciences in Popielno (NE Poland) in April and May 2009. Phoretic mites were found on 26 fleas (15.4%) of the following species: Megabothris walkeri (Rothschild, 1902), Megabothris turbidus (Rothschild, 1909), Ctenophthalmus agyrtes (Heller, 1896), and Hystrichopsylla orientalis (Smit, 1956). The mites were located mainly on abdominal sternites. Among ticks, only one female was positive for mites, whose larvae (hypopi) were found on its legs. A total of 6 species of mites were identified. On I. hexagonus, we found Acarus farris (Oudemans, 1905) (53 larvae), Acarus siro (L., 1758) (2 larvae), Acarus nidicolous (Griffiths, 1970) (1 larva), Caloglyphus rhizoglyphoides (Zachvatkin, 1937) (1 larva), and Histiostoma feroniarum (Dufour, 1904) (28 larvae), whereas on fleas, 79 larvae of Acarus nidicolous, 1 male of Tyrophagus putrescentiae (Schrank, 1781), and 1 unidentified trombiculid larva. The last 2 mite specimens were found on M. turbidus. This is the first report on phoretic association of the flea H. orientalis and the tick I. hexagonus with mites